Development of a maturity assessment model for sustainable tourism - Franz, H. C.; Cruz, A. R. (Current Issues in Tourism, 2025)
Sustainability has become one of the most pressing worldwide concerns for the tourism sector. Destination managers face the challenge of developing strategies and assessing their success in pursuing sustainable development. However, the concept of sustainability is still vague, and existing measurement frameworks are complex and fail to sufficiently include relevant factors such as digitalisation. This article adopts a design science research (DSR) approach to address these issues, creating a conceptual solution for assessing sustainability in tourism destinations and providing directions for destinations’ future development based on a maturity model concept. Objectives for this conceptual solution are developed by critically reviewing relevant literature and existing assessment models for sustainable tourism and operationalised by designing a maturity assessment model for sustainable tourism. To validate this model, interviews with tourism experts and stakeholders are conducted in the Algarve region, Portugal. The study concludes by acknowledging limitations and offering directions for further research.